The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fnins.2023.1125626
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative meta-analysis of acupuncture effects on the motor function of Parkinson's disease patients

Suying Lei,
Jingqi Fan,
Xin Liu
et al.

Abstract: ObjectiveTo explore the association between acupuncture sessions and its effects on the motor function of Parkinson's Disease (PD).MethodsEight databases and two clinical trials registries were searched from inception to August 2022. Randomized controlled trials (RCTs) that compared acupuncture with sham acupuncture, or antiparkinsonian drugs, were included. After qualitative meta-analysis, a non-linear meta regression approach with restricted cubic spline was used to investigate the dose-response relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Notably, the therapeutic impact surpasses placebo acupuncture, highlighting its significant clinical efficacy (10, 11). Several recently published meta-analyses also suggested that acupuncture-related therapies combined with conventional medication showed a moderate or large effect on movement function in patients with PD (6,27). Animal studies have established a scientific foundation supporting the potential of acupuncture in ameliorating symptoms observed in Parkinson's disease (7)(8)(9).…”
Section: Non-pharmacological Approaches In Pd Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the therapeutic impact surpasses placebo acupuncture, highlighting its significant clinical efficacy (10, 11). Several recently published meta-analyses also suggested that acupuncture-related therapies combined with conventional medication showed a moderate or large effect on movement function in patients with PD (6,27). Animal studies have established a scientific foundation supporting the potential of acupuncture in ameliorating symptoms observed in Parkinson's disease (7)(8)(9).…”
Section: Non-pharmacological Approaches In Pd Managementmentioning
confidence: 99%
“…Acupuncture, an ancient technique dating back 2000 years within TCM ( 5 ), has gained widespread utilization by physicians and patients globally in alleviating clinical symptoms in PD. Recent years have witnessed a discernible rise in clinical investigations exploring the use of acupuncture for PD, often reporting positive outcomes ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture, a popular complementary and alternative medicine approach, is recommended as therapy for PD patients based on level B evidence (32,33). Recent meta-analyses have shown that acupuncture in conjunction with conventional medication exhibits a notable positive impact on movement function in PD patients (34,35). Animal studies corroborate these ndings, suggesting acupuncture's potential in alleviating PD symptoms (36,37).…”
Section: Introductionmentioning
confidence: 99%